Microbial Platform for Terpenoid Production: Escherichia coli and Yeast - Wang, Chonglong; Liwei, Mudanguli; Park, Ji-Bin; Jeong, Seong-Hee; Wei, Gongyuan; Wang, Yujun; Kim, Seon-Won (Frontiers in Microbiology, 2018)
Terpenoids also called, isoprenoids, are a large and highly diverse family of natural products with important medical and industrial properties. However, a limited production of terpenoids from natural resources constrains their use of either bulk commodity products or high valuable products. Microbial production of terpenoids from Escherichia coli and yeasts provides a promising alternative owing to available genetic tools in pathway engineering and genome editing, and a comprehensive understanding of their metabolisms. This review summarizes recent progresses in engineering of industrial model strains, Escherichia coli and yeasts, for terpenoids production. With advances of synthetic biology and systems biology, both strains are expected to present the great potential as a platform of terpenoid synthesis.